Transeurasische Verkehrskorridore. Verkehrswege im 21. Jahrhundert. - Hansmann, Armin; Weinand, Johannes (Deutscher Verkehrs-Verl., 2010)
Globalisierung, Urbanisierung und demographischer Wandel die Megatrends im 21. Jahrhundert - prägen auch den Handel und Warenverkehr zwischen Europa und Asien. Insbesondere der asiatische Kontinent, mit seinen vier Mrd. Menschen, seiner steigenden Wirtschaftskraft und ungesättigten Märkten, übt eine starke Anziehungskraft auf die Europäische Gemeinschaft und umgekehrt aus. Europa und Asien rücken näher zusammen. Asien entwickelt sich zunehmend zum wirtschaftlichen Gravitationszentrum des 21. Jahrhunderts und zum wichtigen Handelspartner für Europa.

Europe and Asia are steadily coming closer. Asia and especially China have success fully overcome the economic crisis and the economic growth continues. Trade and the exchange of goods between Europe and Asia benefit from this development. However goods are carried predominantly by large vessels. It is important to realize that in future the shipping routes may become the bottle neck of world trade, thus limiting the exchange of goods between Europe and Asia considerably. Transport initiatives in Europe and Asia pursue a joint aim: they want to make land traffic more attractive, more competitive and more secure. Overburdened ports strained land connections and political decision making contributes to this aim. Considering the facts mentioned above TransEurasian traffic corridors are getting more and more important. Today there is a competition between different transport initiatives of different countries such as TRACECA-Corridor, CAREC-Corridor, NELTI Corridor and the EurAsian- Initiative. What the economyreally needs is an efficient land transport corridor connecting Southwest China, traversing Kazakhstan and Southern Russia on the shortest route possible and finally connecting the Ukraine to the Trans European transport network. A clear focus of resources and financial means on this common Eurasian transport corridor is needed to reach this goal.
TransEurasian Traffic Corridors.
Keywords: Verkehr; Verkehrsweg; Fernverkehr; Wasserverkehr; Straßenverkehr; Schienenverkehr; Straßengüterverkehr; Schienengüterverkehr; Container; Verkehrspolitik; Verkehrsnachfrage; Verkehrsaufkommen; Verkehrsprognose; Verkehrsstatistik; Verkehrskorridor; Containeraufkommen; Grenzüberschreitender Verkehr